PENGEMBANGAN WAWASAN WARGA SEKOLAH LABORATORIUM UNDIKSHA TENTANG SEKOLAH BERWAWASAN LINGKUNGAN DAN MITIGASI BENCANA (SWALIBA) - Astawa, Ida Bagus Made; Budiarta, I Gede; Treman, I Wayan; Sarmita, I Made (JURNAL WIDYA LAKSANA, 2022)
Environmental conservation in the context of global warming and Indonesia's geology located in the Pacific Ring of Fire area is the basis used to launch the Environmentally Insight School and Disaster Mitigation Program (SWALIBA) in Indonesia as a form of character education, especially in schools located in vulnerable areas. disaster. This program aims to create a young generation with character of love and care for the environment and understand how to respond to disasters. The Undiksha Laboratory School is geologically located in the Seririt Fault area which is very unstable so it is prone to earthquakes and tsunamis. In this regard, Community Service (PkM) is carried out with one of the activities being to provide SWALIBA insight to the residents of the Undiksha Laboratory School (Managers, Directors, Teachers, and Employees). Providing insight using the Education method with three stages (providing material, discussion, and evaluation) which is carried out online through webinars. The results of the service carried out showed that the SWALIBA insight of the Undiksha Laboratory School residents was classified as 'good' (Mean = 74.73). As a first step to developing the SWALIBA Program at the Undiksha Laboratory School, this good insight is needed, because it will be able to contribute to the development of the program to be designed.